2009
DOI: 10.1039/b910977c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of highly enantiomerically enriched planar chiral ruthenium complexes via Pd-catalysed asymmetric hydrogenolysis

Abstract: Key elements in this communication are a very efficient microwave synthesis of [RuCp(naphthalene)][PF(6)], the precursor of [RuCp(CH(3)CN)(3)][PF(6)], and a Pd-catalysed asymmetric hydrogenolysis to afford planar chiral ruthenium complexes with high levels of enantioselectivity using a bulky chiral phosphoramidite ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 47 publications
0
36
0
1
Order By: Relevance
“…After careful investigations, we found that phosphoramidite L1 was recovered as a phosphoramidite-borane complex at the end of the reaction. The presence of borane was confirmed by 11 B NMR analysis (-39.6 ppm) and the 31 P{ 1 H} NMR signal is in accordance with the few examples of isolated aminophosphane-borane adducts. [9] Upon hydride transfer to Pd, LiBH 4 liberated borane, which formed an adduct with ligand L1, thus depleting the reaction of the essential chiral information.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…After careful investigations, we found that phosphoramidite L1 was recovered as a phosphoramidite-borane complex at the end of the reaction. The presence of borane was confirmed by 11 B NMR analysis (-39.6 ppm) and the 31 P{ 1 H} NMR signal is in accordance with the few examples of isolated aminophosphane-borane adducts. [9] Upon hydride transfer to Pd, LiBH 4 liberated borane, which formed an adduct with ligand L1, thus depleting the reaction of the essential chiral information.…”
Section: Resultsmentioning
confidence: 49%
“…[11] 6). Owing to solubility and relative stability issues, reaction conditions had to be slightly modified from those optimal for 1.…”
Section: Resultsmentioning
confidence: 99%
“…These were used in catalytic asymmetric hydrogenolysis to access planar chiral complexes thus opening a new route of access to this family of compounds ( Figure 2). [24,[34][35][36] Our earlier findings in the study of Cr(CO) 3 complexes of 1,4-naphthoquinone, 1,4-dihydroxynaphthalene, and 1,4-tetralindione [37][38][39][40] prompted us to next investigate analogous organometallics containing the isolobal CpRu + fragment (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…In the first part of this article, we disclose details of the same route but using microwave heating. [24] This dramatically shortens the reaction time while keeping the yield high (Scheme 2, bottom). We also show that a range of simple cationic Ru(II)(arene)Cp complexes are accessible through this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Kündig et al reported high enantioselectivities for the asymmetric hydrogenolysis of an arylbromo bond in achiral arene complexes 95, which they converted to enantiomerically enriched arene complexes 96 using palladium complexes derived from chiral phosphorus ligands 50 (Scheme 10). 82,83,84 Highly enantioenriched, planar, fused arene complexes were accessible by hydrogenolysis of one of the two CBr bonds in the substrate, using LiBH 4 in the presence of chiral palladium complexes derived from the phosphoramidite ligand 97. Alternative reducing agents were also studied; 55 however, they either failed to promote the desired transformation, or gave lower enantioselectivity than did LiBH 4 .…”
Section: Hydrogenolysis Of Dihaloaromatic Compoundsmentioning
confidence: 99%